Anodal Contralesional tDCS Enhances CST Excitability Bilaterally in an Adolescent with Hemiparetic Cerebral Palsy: A Brief Report. (3rd April 2023) - Delatorre, Rodrigo G.; Sutter, Ellen N.; Nemanich, Samuel T.; Krach, Linda E.; Meekins, Gregg; Feyma, Timothy; Gillick, Bernadette T.
ABSTRACT: Hemiparetic cerebral palsy (HCP), weakness on one side of the body typically caused by perinatal stroke, is characterized by lifelong motor impairments related to alterations in the corticospinal tract (CST). CST reorganization could be a useful biomarker to guide applications of neuromodulatory interventions, such as transcranial direct current stimulation (tDCS), to improve the effectiveness of rehabilitation therapies. We evaluated an adolescent with HCP and CST reorganization who demonstrated persistent heightened CST excitability in both upper limbs following anodal contralesional tDCS. The results support further investigation of targeted tDCS as an adjuvant therapy to traditional neurorehabilitation for upper limb function.